Traditional folk music of Kosovo and Metohia in art music - Pavlović Biljana M. (Baština, 2013)
In this paper the author considers art music works of Serbian composers, based on the traditional folk music of Kosovo and Metohia. The aim is to stimulate interest in listening to and familiarize with the national art music in the primary school music teaching. Compositions inspired by traditional music of Kosovo and Metohia, as well as composition which represent treatment of folk songs of this region, have been investigated in order to propose to listen in class. By listening to these works contribution is being made to the introduction of national art music, as well as the affirmation of Kosovo and Metohia national musical creativity.